Congenital Heart Disease in a Tertiary Care NICU; Pattern, Risk Factors and Outcome (Bangladesh Journal of Child Health, 2024)
Background: Identification of congenital heart disease (CHD) is increasing, may be due to advancement of diagnostic technology and availability of trained man power. Several studies have been conducted in Bangladesh to identify the prevalence and pattern of CHD but paucity of data regarding etiology and outcome.Objective: The aim of this study is to identify the frequency and risk factors of so that preventive measures can be taken.Methods: This retrospective case control study was conducted in the neonatal intensive care unit (NICU), BSMMU, Dhaka from January 2021 to June 2022. All admitted neonates in NICU with the diagnosis of CHD were considered as cases. Twice number of newborn having gestational age and birth weight matched neonates diagnosed other than CHD in NICU were considered as control. Data were extracted from the Medical records of patient files and computer electronic data records of “Newborn Birth Defect (NBBD) surveillance in Bangladesh.” The level of significance was set at 5% (P